(untitled) (International relations and international law Journal, 2018)
This article analyzes the works of Western researchers on Central Asia between 2010 and 2016. We consider the point of view of various authors that focus not only on issues of geopolitics, security and international position of Central Asia, but are dedicated to the internal problems of individual countries in the region, their political and socio-economic development. By the end of the 2000s the impression that foreign interest in the Central Asian region has exhausted itself, that everything has already been written. It seems that the West has lost the geopolitical interest in Central Asia, which is supported by the presence of US and NATO forces in Afghanistan. And all the changing dramatically: on the one hand, the West is scared Russia’s desire to speed up the creation of the Eurasian Union; on the other – strengthening of China in Central Asia is also not satisfied with the Western strategists. It also may include factors of Iran, India and Afghanistan, again, to understand that the geopolitical struggle over Central Asia does not disappear, but is entering a new phase. Key words: Central Asia, Western researches, security issue, Eurasia, «Greater Central Asia», historiography, political and socio-economic development of Central Asian states.